Particular fuzzy subsets on topologies generated by fuzzy relations - Khaoui, Nada ErReyhane; Supervisor: Milles, Soheyb; Co-Supervisor: Zedam, Lemnaouar (University of M'sila, 2023)
In this memoire, we study a particular subsets which are the ideals and filters on a lattice of open sets in topology generated by fuzzy relation. Moreover, we study characterizations of these particular subsets with some related results.
Keywords: Fuzzy relation, Fuzzy topology, Lattice, Fuzzy ideal, Fuzzy filter.